Effect of VOx Species and Support on Coke Formation and Catalyst Stability in Nonoxidative Propane Dehydrogenation. Issue 11 (12th May 2015) - Sokolov, Sergey; Bychkov, Victor Yu.; Stoyanova, Mariana; Rodemerck, Uwe; Bentrup, Ursula; Linke, David; Tyulenin, Yurij P.; Korchak, Vladimir N.; Kondratenko, Evgenii V.
Abstract VOx/SiO2–Al2O3 catalysts were prepared by grafting vanadyl acetylacetonate onto the supports with a SiO2 content between 0 and 100 wt. %. The degree of polymerization of VOx species and acidity both of pristine supports and the catalysts were evaluated. To determine their on‐stream stability and carbon deposition activity in nonoxidative propane dehydrogenation, continuous‐flow tests and in situ thermogravimetric measurements were performed. The rate constants of catalyst deactivation and carbon deposition were derived from kinetic evaluation of these experiments. Gathered experimental evidence pointed out that VOx species were significantly more active for coke formation than acid sites of the supports. The rate constant of carbon formation was found to increase with the degree of polymerization of VOx species, whereas no correlation between catalyst acidity and the rate constants of coking or deactivation could be drawn.